Impact of clinical and subclinical coronary artery disease as assessed by coronary artery calcium in COVID-19. (July 2021) - Scoccia, Alessandra; Gallone, Guglielmo; Cereda, Alberto; Palmisano, Anna; Vignale, Davide; Leone, Riccardo; Nicoletti, Valeria; Gnasso, Chiara; Monello, Alberto; Khokhar, Arif; Sticchi, Alessandro; Biagi, Andrea; et al.
Abstract: Background and aims: The potential impact of coronary atherosclerosis, as detected by coronary artery calcium, on clinical outcomes in COVID-19 patients remains unsettled. We aimed to evaluate the prognostic impact of clinical and subclinical coronary artery disease (CAD), as assessed by coronary artery calcium score (CAC), in a large, unselected population of hospitalized COVID-19 patients undergoing non-gated chest computed tomography (CT) for clinical practice. Methods: SARS-CoV 2 positive patients from the multicenter (16 Italian hospitals), retrospective observational SCORE COVID-19 (calcium s core for CO VID-19 R isk E valuation) registry were stratified in three groups: (a) "clinical CAD" (prior revascularization history), (b) "subclinical CAD" (CAC >0), (c) "No CAD" (CAC = 0). Primary endpoint was in-hospital mortality and the secondary endpoint was a composite of myocardial infarction and cerebrovascular accident (MI/CVA). Results: Amongst 1625 patients (male 67.2%, median age 69 [interquartile range 58–77] years), 31%, 57.8% and 11.1% had no, subclinical and clinical CAD, respectively. Increasing rates of in-hospital mortality (11.3% vs. 27.3% vs. 39.8%, p < 0.001) and MI/CVA events (2.3% vs. 3.8% vs. 11.9%, p < 0.001) were observed for patients with no CAD vs. subclinical CAD vs clinical CAD, respectively. The association with in-hospital mortality was independent of in-study outcome predictors (age, peripheral artery disease, active cancer, hemoglobin, C-reactive protein, LDH, aerated lung volume): subclinical CAD vs. No CAD: adjusted hazard ratio (adj-HR) 2.86 (95% confidence interval [CI] 1.14–7.17, p= 0.025); clinical CAD vs. No CAD: adj-HR 3.74 (95% CI 1.21–11.60, p= 0.022). Among patients with subclinical CAD, increasing CAC burden was associated with higher rates of in-hospital mortality (20.5% vs. 27.9% vs. 38.7% for patients with CAC score thresholds≤100, 101–400 and > 400, respectively, p < 0.001). The adj-HR per 50 points increase in CAC score 1.007 (95%CI 1.001–1.013, p= 0.016). Cardiovascular risk factors were not independent predictors of in-hospital mortality when CAD presence and extent were taken into account. Conclusions: The presence and extent of CAD are associated with in-hospital mortality and MI/CVA among hospitalized patients with COVID-19 disease and they appear to be a better prognostic gauge as compared to a clinical cardiovascular risk assessment. Graphical abstract: Image 1 Highlights: The potential impact of coronary atherosclerosis, as detected by coronary artery calcium, on clinical outcomes in COVID-19 remains unsettled. If coronary artery calcium, a marker of atherosclerotic burden, may be a better gauge of COVID-19 outcomes than clinical profile is unsettled. Clinical and subclinical coronary artery disease assessed by coronary artery calcium score is associated with in-hospital mortality. Cardiovascular risk factors are not independently associated with in-hospital mortality when coronary atherosclerosis is considered.